Performance Test of Homemade Control Materials from Addition and Spike Placebo Simulation on Urine Chloride Examination with Fantus Method - Titin Aryani (Fakultas Ilmu Kesehatan Universitas Setia Budi Surakarta, 2021)
The background of this research was to examine the performance of homemade urine control materials on urine chloride examination. This study was aimed to test the performance of homemade control materials from addition and spike placebo simulation on urine chloride examination using the Fantus method. This research applied an experimental research method. The stages of the study started with standardization of AgNO3 solution, preparation of urine control materials from addition and spike placebo simulation, as well as calculation of accuracy (%R), bias (%d) and coefficient of variation (%CV). The results showed that the normal and pathological levels of accuracy in the urine control materials from addition were 109.55% and 104.30%, while the accuracy values (%R) ​​for urine control materials from spike placebo simulation, for the normal and pathological levels, were high, 110.07% and 104.54%. The bias values (%d) obtained in the urine control materials from addition with normal and high pathological levels were 9.55% and 4.30% bias, while the bias values (%d) in the urine control materials from spike placebo simulation with normal and high pathological levels were 10.07% and 4.54%. The coefficient variation (%CV) values ​​in urine control materials from addition at normal and pathological high levels were 3.75% and 3.07%, while the %CV values ​​in urine control materials from spike placebo simulation at normal and high pathological levels were 4.55% and 3.11%. This study concludes that based on the accuracy (%R) and bias (%d) parameters, the homemade control materials from addition and spike placebo simulation have relatively good performance for urine chloride examination using the Fantus method. Meanwhile, based on the parameter of coefficient of variation (%CVV), the homemade control materials from the addition and spike placebo simulation have slightly lower performance for examining urine chloride with the Fantus method.